Humidity‐controlled cold storage of Neoseiulus californicus (Acari: Phytoseiidae): effects on male survival and reproductive ability. (9th August 2012) - Ghazy, N. A.; Suzuki, T.; Amano, H.; Ohyama, K.
Abstract Humidification can suppress water loss from an organism and has great potential for improving the cold storage of short‐lived arthropods, such as predatory mites. The effectiveness of humidity‐controlled cold storage was recently verified for Neoseiulus californicus (McGregor) females but was not examined for males. Combining both males and females in one storage protocol might increase the predator population because it would enhance the opportunity for multiple mating, which is necessary for females to maximize their egg production. Newly emerged adult males were stored at an air temperature of 5°C and relative humidity (RH) of 100% or 80%. The median survival time (LT50) was 32 days at 100% RH and 14 days at 80% RH; the survival curves differed significantly. Males stored at 100% RH for 0, 10, 20 and 30 days were introduced to virgin females for mating at 25°C to evaluate their reproductive ability. The pre‐oviposition period was significantly prolonged in the females mated with males stored for ≥20 days. No negative effects of storage were observed on the oviposition period, total number of eggs or net reproduction rate (R0) in the females mated with males stored for ≤20 days or on the mean generation time (T) for those stored for 30 days. A slight decrease in the intrinsic rate of increase (rm) was observed in the females mated with males stored for ≥20 days. Our storage method can preserve N. californicus males for 20 days with only a minor reduction in their survival and reproductive ability.